Advances in imaging findings of preeclampsia-related reversible posterior leukoencephalopathy syndrome - Zhang, Nan; Yang, Linfeng; Han, Aiqing; Wang, Yuanyuan; Zhao, Guiwu; Wang, Yue; Chen, Tao (Frontiers in Neuroscience, 2023)
Preeclampsia (PE)-related reversible posterior leukoencephalopathy syndrome (RPLS) is a common complication of hypertensive disorders of pregnancy. The syndrome usually occurs after 20 weeks of gestation and can lead to brain injury. Severe headache, seizures, disturbance of consciousness, and other neurological symptoms may occur in severe cases. PE-RPLS has high morbidity and mortality rates and seriously damages maternal and fetal health. In recent years, the continuous advancement of medical imaging technology has provided an important imaging basis for the early diagnosis and prognostic evaluation of RPLS. This article mainly details the research status of the etiology and pathogenesis of PE-RPLS and describes its characteristic imaging findings, especially MRI findings, to provide new insights into its early diagnosis, early treatment, and improvement of prognosis.